Anisotropic transport of microalgae Chlorella vulgaris in microfluidic channel *Project supported by the Science Fund from the Ministry of Higher Education of Malaysia under the Fundamental Research Grant Scheme (Grant No. FRGS: FP057-2014A) and the Fund from the University of Malaya Research Grant (Grant No. UMRG: RP020A-14AFR). (August 2017) - Ishak, Nur Izzati; Muniandy, S V; Periasamy, Vengadesh; Ng, Fong-Lee; Phang, Siew-Moi
Abstract : In this work, we study the regional dependence of transport behavior of microalgae Chlorella vulgaris inside microfluidic channel on applied fluid flow rate. The microalgae are treated as spherical naturally buoyant particles. Deviation from the normal diffusion or Brownian transport is characterized based on the scaling behavior of the mean square displacement (MSD) of the particle trajectories by resolving the displacements in the streamwise (flow) and perpendicular directions. The channel is divided into three different flow regions, namely center region of the channel and two near-wall boundaries and the particle motions are analyzed at different flow rates. We use the scaled Brownian motion to model the transitional characteristics in the scaling behavior of the MSDs. We find that there exist anisotropic anomalous transports in all the three flow regions with mixed sub-diffusive, normal and super-diffusive behavior in both longitudinal and transverse directions.